Inotuzumab ozogamicin in combination with low‐intensity chemotherapy (mini‐HCVD) with or without blinatumomab versus standard intensive chemotherapy (HCVAD) as frontline therapy for older patients with Philadelphia chromosome‐negative acute lymphoblastic leukemia: A propensity score analysis. Issue 15 (15th April 2019) - Jabbour, Elias J.; Sasaki, Koji; Ravandi, Farhad; Short, Nicholas J.; Garcia‐Manero, Guillermo; Daver, Naval; Kadia, Tapan; Konopleva, Marina; Jain, Nitin; Cortes, Jorge; Issa, Ghayas C.; Jacob, Jovitta; et al.
Abstract : Background: The outcome of older patients with newly diagnosed, Philadelphia chromosome (Ph)‐negative acute lymphoblastic leukemia (ALL) is poor. The combination of targeted therapy with low‐intensity chemotherapy is safe and effective. The objective of the current analysis was to compare the outcome of patients who received a combination of inotuzumab ozogamicin plus low‐intensity chemotherapy (mini–hyperfractionated cyclophosphamide, vincristine, and dexamethasone [mini‐HCVD]) with or without blinatumomab versus the outcome of those who received the standard, intensive, hyperfractionated cyclophosphamide, vincristine, doxorubicin, and dexamethasone (HCVAD) regimen. Methods: The authors analyzed 135 older patients with newly diagnosed, Ph‐negative ALL who were treated prospectively with standard HCVAD (n = 77) or with the combination of inotuzumab ozogamicin plus mini‐HCVD with or without blinatumomab (n = 58). A propensity score analysis was conducted using 1:1 matching using the nearest neighbor matching method. Results: Propensity score matching identified 38 patients in each cohort. The antibody plus low‐intensity chemotherapy combination induced higher response rates (98% vs 88%), with lower rates of early death (0% vs 8%) and lower rates of death in complete remission (5% vs 17%). With propensity score matching, the 3‐year event‐free survival rates for patients who received HCVAD and those who received the combination of inotuzumab ozogamicin plus mini‐HCVD with or without blinatumomab were 34% and 64%, respectively ( P  = .003), and the 3‐year overall survival rates were 34% and 63%, respectively ( P  = .004). By multivariate analysis, age ( P  = .019; hazard ratio, 1.045) and the combination of inotuzumab plus mini‐HCVD with or without blinatumomab ( P  = .020; hazard ratio, 0.550) were identified as independent prognostic factors for survival. Conclusions: The combination of inotuzumab ozogamicin plus mini‐HCVD with or without blinatumomab is safe and effective in older patients with newly diagnosed, Ph‐negative ALL and confers a better outcome compared with standard HCVAD chemotherapy. Abstract : The combination of inotuzumab ozogamicin plus mini–hyperfractionated cyclophosphamide, vincristine, and dexamethasone with or without blinatumomab is safe and effective in older patients with newly diagnosed, Philadelphia chromosome‐negative acute lymphoblastic leukemia and confers a better outcome compared with standard hyperfractionated cyclophosphamide, vincristine, doxorubicin, and dexamethasone chemotherapy.